Automatic Restoration of Power Supply in Distribution Systems by Computer-Aided Technologies - Bernardon, Daniel; Sperandio, Mauricio; Garcia, Vinícius; Pfitscher, Luciano; Reck, Wagner (IntechOpen, 2012)
None